Gold Mineralization of New Caledonia (The Australasian Institute of Mining and Metallurgy, 1987)
New Caledonia is a major metallogenic unit of the south-western Pacific Rim. Its mineral production is of world significance and it has an unusually well diversified mining history. New Caledonia's main metallogenetic potential is, however, associated with its unique ophiolitic complex and its important mineral- izations of nickel, chrome, cobalt and iron. Gold has been found in all the four basic tectonic elements of New Caledonia: the Central Massif, the West Coast basalts, the ophiolitic complex and the Caledonian North. Some analogies are attempted. Only the Caledonian North has supported mining operations (213 kg Au). More recently tenuous gold indications have been found within the ophiolitic complex, possibly associated with Oligocene plutonism.